The Interpretation of Strangeness and its Impact on the Local Society in Beregdéda, Transcarpathia - Kohut-Ferki, Julianna (Ethnographica et Folkloristica Carpathica, 2023)
My work focuses on the different patterns of experiencing strangeness. Based on my ethnographic fieldwork in Beregdéda, Transcarpathia, Ukraine, I try to reflect on why the articulation of strangeness becomes necessary, and how does the appearance of the stranger modify, erode, rebuild or create symbolic boundaries between the Hungarian-Ukrainian-Gypsy ethnic groups living together. At the time of the fieldwork, in spring 2015, the Ukrainian-Russian war conflict provided a breeding ground for stereotypical perceptions of ethnicity, while the appearance of the stranger tourist also led to the strengthening of the relationship between Ukrainians, Hungarians and Gypsies in the local society, and to the formation of a united front. The understanding of the stranger is constantly changing in line with the various regional and global cultural and economic processes and is formulated with individual interests in mind.